Gender Differences in Neurological Emergencies Part II: A Consensus Summary and Research Agenda on Traumatic Brain Injury. (24th November 2014) - Wright, David W.; Espinoza, Tamara R.; Merck, Lisa H.; Ratcliff, Jonathan J.; Backster, Anika; Stein, Donald G.; Miner, James
Abstract Traumatic brain injury (TBI) is a major cause of death and disability worldwide. There is strong evidence that gender and sex play an important role across the spectrum of TBI, from pathophysiology to clinical care. In May 2014, Academic Emergency Medicine held a consensus conference "Gender‐Specific Research in Emergency Care: Investigate, Understand, and Translate How Gender Affects Patient Outcomes." A TBI working group was formed to explore what was known about the influence of sex and gender on TBI and to identify gaps for future research. The findings resulted in four major recommendations to guide the TBI research agenda.